Method for prolonging service life of lead salt single flow battery
By actively depositing the lead active material skeleton on the surface of the lead salt single-flow battery electrode, the problem of free lead ion consumption in the first cycle is solved, and the service life and circulation efficiency of the battery are improved.
Patent Information
- Application Number
- CN202411206825.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-27
AI Technical Summary
The formation of the deposition skeleton of the lead-salt single-flow battery in the first cycle leads to a decrease in the concentration of free lead ions, which seriously shortens the battery's service life.
The lead active material skeleton is actively deposited on the electrode surface, and electrochemical deposition is performed by electrochemical deposition using fluoroboric acid electrolyte and graphite electrode to reduce the consumption of free lead ions in the first cycle of the battery.
It effectively improves the cycle life and first cycle efficiency of lead single-flow batteries, reduces lead ion consumption in the electrolyte, and improves the battery service life and long cycle efficiency.
Smart Images

Figure CN119208628A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lead salt single-flow batteries, and in particular to a method for improving the service life of lead salt single-flow batteries. Background Art
[0002] Lead salt single flow battery uses a single electrolyte and does not require expensive proton exchange membranes, so the construction cost of the energy storage system is relatively low. And because it is a liquid battery, there is no risk of explosion or fire, and it is safe and reliable. Lead salt single flow battery adopts a modular structure, and the battery capacity and power can be adjusted by adjusting the electrolyte volume and electrode sheet area.
[0003] In the lead salt single-liquid flow energy storage system, under the same electrode plate area, the actual capacity and life of the battery are determined by the concentration of free lead ions in the electrolyte. During the first charging process, PbO will be generated on the positive electrode surface. x (x=1~2) lead active material skeleton, the deposition of active material in subsequent cycles is based on the skeleton. However, during the discharge process, PbO x The skeleton cannot be dissolved, which will lead to incomplete discharge and a large amount of active substances remaining in both the positive and negative electrodes.
[0004] The formation of the deposition skeleton is only evident in the first cycle, so the coulombic efficiency of the first cycle is generally low (45%-55%). The formation of the deposition skeleton will cause a decrease in the concentration of free lead ions in the electrolyte, seriously shortening the service life of the lead single-flow battery. Summary of the invention
[0005] The purpose of the present invention is to provide a method for improving the service life of a lead single-flow battery, which solves the problem that the formation of a deposition skeleton in the first cycle of a lead salt single-flow battery affects the service life, and can effectively reduce the reduction in lead ion concentration in the first charge and discharge cycle of the battery, thereby improving the battery cycle life.
[0006] The technical solution adopted by the present invention is: a method for improving the service life of a lead single-flow battery, wherein an electrode is pretreated by electrochemical deposition before use, and a layer of lead active material skeleton is actively deposited on its surface to reduce the consumption of free lead ions in the first cycle of the battery, thereby improving the service life.
[0007] The technical solution adopted by the present invention is also characterized in that:
[0008] Further, the method for improving the service life of the lead single-flow battery is specifically implemented according to the following steps:
[0009] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0010] Step 2, electrochemically depositing the electrode in step 1 in a fluoroboric acid or lead fluoroborate solution of corresponding concentration at a certain current density;
[0011] Step 3: Assembling the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead salt single-flow battery with a longer cycle life.
[0012] Furthermore, step 1 is specifically implemented according to the following steps:
[0013] Step 1.1, dissolving lead oxide in fluoroboric acid, stirring until clear and then fixing the volume to obtain an electrolyte;
[0014] Step 1.2: After cutting and polishing the graphite sheet, fix the back side to the copper sheet with conductive glue and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0015] Furthermore, step 2 is specifically implemented according to the following steps:
[0016] Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition;
[0017] Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
[0018] Furthermore, the electrolyte used for electrochemical deposition of the electrode is c(Pb 2+ ) is 0.5mol / L~1.5mol / L, the deposition time is 5min, and the current density used for deposition is 10mA / cm 2 ~40mA / cm 2 .
[0019] The present invention provides a method for increasing the service life of a lead single-liquid flow battery. Compared with the traditional method, the present invention has the following beneficial effects:
[0020] 1. The present invention adopts fluoroboric acid as the electrolyte, and has high cycle efficiency.
[0021] 2. The present invention performs lead active skeleton deposition treatment on the lead single-flow battery electrode, which can effectively improve the battery's first cycle efficiency, effectively reduce the lead ion consumption in the first cycle electrolyte, and improve the battery's service life and long cycle coulombic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scan of the positive electrode of a lead-salt single-flow battery after charging only;
[0023] Figure 2 This is a scan of the positive electrode of a lead-salt single-flow battery after one charge and discharge cycle;
[0024] Figure 3This is a positive electrode scanning diagram after being processed by the method of the present invention. DETAILED DESCRIPTION
[0025] The present invention will be further described below through the accompanying drawings and specific embodiments.
[0026] The present invention discloses a method for improving the service life of a lead single-liquid flow battery, wherein the electrode is pretreated before use, and a layer of lead active material skeleton is actively deposited on its surface, such as Figure 3 As shown, in order to reduce the consumption of free lead ions in the first cycle of the battery, thereby increasing the service life, the following steps are specifically included:
[0027] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0028] Step 2, electrochemically depositing the electrode in step 1 in a solution of corresponding concentration (fluoroboric acid / lead fluoroborate) at a certain current density;
[0029] Step 3: Assemble the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead salt single-flow battery with a longer cycle life.
[0030] The present invention is also characterized in that:
[0031] The size of the graphite electrode is 10mm×10mm, which is used for electrochemical deposition of the electrolyte used for the electrode. 2+ ) is 0.5mol / L~1.5mol / L, the deposition time is 5min, and the current density used for deposition is 10mA / cm 2 ~40mA / cm 2 . c(Pb 2+ ) is 1.5mol / L.
[0032] Step 1 is implemented as follows:
[0033] Step 1.1, dissolve lead oxide in fluoroboric acid, stir until clear and then adjust the volume to obtain an electrolyte.
[0034] Step 1.2: After cutting and polishing the graphite sheet, fix the back side to the copper sheet with conductive glue and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0035] Step 2 is implemented as follows:
[0036] Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition;
[0037] Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
[0038] The present invention is further described below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0039] Example 1
[0040] The electrode is pretreated before use, and a layer of lead oxide is actively deposited on its surface to improve the initial performance of the lead single-liquid flow battery and thus increase its service life.
[0041] The above deposition uses c(Pb 2+ )=0.5mol / L, deposition time is 5min, deposition current density is 10mA / cm 2 .
[0042] The above electrolyte, electrode and electrochemical deposition are carried out according to the following steps:
[0043] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0044] Step 2, electrochemically depositing the electrode in step 1 in a solution of corresponding concentration (fluoroboric acid / lead fluoroborate) at a certain current density;
[0045] Step 3: Assemble the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead single-flow battery with a longer cycle life.
[0046] Step 1 is implemented as follows:
[0047] Step 1.1, dissolve lead oxide in fluoroboric acid, stir until clear and then adjust the volume to obtain an electrolyte.
[0048] Step 1.2: Cut and grind the graphite sheet into a size of 10 mm × 10 mm, fix the back side to the copper sheet with conductive glue, and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0049] Step 2 is implemented as follows:
[0050] Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition;
[0051] Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
[0052] All chemicals used were of analytical grade.
[0053] The battery obtained in Example 1 was subjected to charge and discharge cycles at 25 mA / cm 2Under the charging condition, the battery was charged for 5 hours and then discharged. The discharge cut-off condition was that the voltage was lower than 1V. After 100 cycles, the lead ion concentration in the remaining electrolyte and the average energy efficiency of the last five cycles were measured to be 1.385 mol / L and 94.8%, respectively.
[0054] Example 2
[0055] The electrode is pretreated before use, and a layer of lead oxide is actively deposited on its surface to improve the initial performance of the lead single-liquid flow battery and thus increase its service life.
[0056] The above coating adopts c(Pb 2+ )=0.5mol / L, deposition time is 5min, deposition current density is 25mA / cm 2 .
[0057] The above electrolyte, electrode and electrochemical deposition are carried out according to the following steps:
[0058] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0059] Step 2, electrochemically depositing the electrode in step 1 in a solution of corresponding concentration (fluoroboric acid / lead fluoroborate) at a certain current density;
[0060] Step 3: Assemble the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead single-flow battery with a longer cycle life.
[0061] Step 1 is implemented as follows:
[0062] Step 1.1, dissolve lead oxide in fluoroboric acid, stir until clear and then adjust the volume to obtain an electrolyte.
[0063] Step 1.2: Cut and grind the graphite sheet into a size of 10 mm × 10 mm, fix the back side to the copper sheet with conductive glue, and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0064] Step 2 is implemented as follows:
[0065] Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition;
[0066] Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
[0067] All chemicals used were of analytical grade.
[0068] The battery obtained in Example 2 was subjected to charge and discharge cycles at 25 mA / cm 2Under the charging condition, the battery was charged for 5 hours and then discharged. The discharge cut-off condition was that the voltage was lower than 1V. After 100 cycles, the lead ion concentration in the remaining electrolyte and the average energy efficiency of the last five cycles were measured to be 1.403 mol / L and 95.3%, respectively.
[0069] Example 3
[0070] The electrode is pretreated before use, and a layer of lead oxide is actively deposited on its surface to improve the initial performance of the lead single-liquid flow battery and thus increase its service life.
[0071] The above coating adopts c(Pb 2+ )=0.5mol / L, deposition time is 5min, deposition current density is 40mA / cm 2 .
[0072] The above electrolyte, electrode and electrochemical deposition are carried out according to the following steps:
[0073] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0074] Step 2, electrochemically depositing the electrode in step 1 in a solution of corresponding concentration (fluoroboric acid / lead fluoroborate) at a certain current density;
[0075] Step 3: Assemble the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead single-flow battery with a longer cycle life.
[0076] Step 1 is implemented as follows:
[0077] Step 1.1, dissolve lead oxide in fluoroboric acid, stir until clear and then adjust the volume to obtain an electrolyte.
[0078] Step 1.2: Cut and grind the graphite sheet into a size of 10 mm × 10 mm, fix the back side to the copper sheet with conductive glue, and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0079] Step 2 is implemented as follows:
[0080] Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition;
[0081] Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
[0082] All chemicals used were of analytical grade.
[0083] The battery obtained in Example 3 was subjected to charge and discharge cycles at 25 mA / cm 2Under the charging condition, the battery was charged for 5 hours and then discharged. The discharge cut-off condition was that the voltage was lower than 1V. After 100 cycles, the lead ion concentration in the remaining electrolyte and the average energy efficiency of the last five cycles were measured to be 1.371 mol / L and 93.3%, respectively.
[0084] Example 4
[0085] The electrode is pretreated before use, and a layer of lead oxide is actively deposited on its surface to improve the initial performance of the lead single-liquid flow battery and thus increase its service life.
[0086] The above coating adopts c(Pb 2+ )=1.0mol / L, deposition time is 5min, deposition current density is 10mA / cm 2 .
[0087] The above electrolyte, electrode and electrochemical deposition are carried out according to the following steps:
[0088] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0089] Step 2, electrochemically depositing the electrode in step 1 in a solution of corresponding concentration (fluoroboric acid / lead fluoroborate) at a certain current density;
[0090] Step 3: Assemble the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead single-flow battery with a longer cycle life.
[0091] Step 1 is implemented as follows:
[0092] Step 1.1, dissolve lead oxide in fluoroboric acid, stir until clear and then adjust the volume to obtain an electrolyte.
[0093] Step 1.2: Cut and grind the graphite sheet into a size of 10 mm × 10 mm, fix the back side to the copper sheet with conductive glue, and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0094] Step 2 is implemented as follows:
[0095] Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition;
[0096] Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
[0097] All chemicals used were of analytical grade.
[0098] The battery obtained in Example 4 was subjected to charge and discharge cycles at 25 mA / cm 2Under the charging condition, the battery was charged for 5 hours and then discharged. The discharge cut-off condition was that the voltage was lower than 1V. After 100 cycles, the lead ion concentration in the remaining electrolyte and the average energy efficiency of the last five cycles were measured to be 1.432 mol / L and 97.7%, respectively.
[0099] Example 5
[0100] The electrode is pretreated before use, and a layer of lead oxide is actively deposited on its surface to improve the initial performance of the lead single-liquid flow battery and thus increase its service life.
[0101] The above coating adopts c(Pb 2+ )=1.0mol / L, deposition time is 5min, deposition current density is 25mA / cm 2 .
[0102] The above electrolyte, electrode and electrochemical deposition are carried out according to the following steps:
[0103] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0104] Step 2, electrochemically depositing the electrode in step 1 in a solution of corresponding concentration (fluoroboric acid / lead fluoroborate) at a certain current density;
[0105] Step 3: Assemble the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead single-flow battery with a longer cycle life.
[0106] Step 1 is implemented as follows:
[0107] Step 1.1, dissolve lead oxide in fluoroboric acid, stir until clear and then adjust the volume to obtain an electrolyte.
[0108] Step 1.2: Cut and grind the graphite sheet into a size of 10 mm × 10 mm, fix the back side to the copper sheet with conductive glue, and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0109] Step 2 is implemented as follows:
[0110] Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition;
[0111] Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
[0112] All chemicals used were of analytical grade.
[0113] The battery obtained in Example 5 was subjected to charge and discharge cycles at 25 mA / cm 2Under the charging condition, the battery was charged for 5 hours and then discharged. The discharge cut-off condition was that the voltage was lower than 1V. After 100 cycles, the lead ion concentration in the remaining electrolyte and the average energy efficiency of the last five cycles were measured to be 1.457 mol / L and 98.5%, respectively.
[0114] Example 6
[0115] The electrode is pretreated before use, and a layer of lead oxide is actively deposited on its surface to improve the initial performance of the lead single-liquid flow battery and thus increase its service life.
[0116] The above coating adopts c(Pb 2+ )=1.0mol / L, deposition time is 5min, deposition current density is 40mA / cm 2 .
[0117] The above electrolyte, electrode and electrochemical deposition are carried out according to the following steps:
[0118] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0119] Step 2, electrochemically depositing the electrode in step 1 in a solution of corresponding concentration (fluoroboric acid / lead fluoroborate) at a certain current density;
[0120] Step 3: Assemble the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead single-flow battery with a longer cycle life.
[0121] Step 1 is implemented as follows:
[0122] Step 1.1, dissolve lead oxide in fluoroboric acid, stir until clear and then adjust the volume to obtain an electrolyte.
[0123] Step 1.2: Cut and grind the graphite sheet into a size of 10 mm × 10 mm, fix the back side to the copper sheet with conductive glue, and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0124] Step 2 is implemented as follows:
[0125] Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition;
[0126] Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
[0127] All chemicals used were of analytical grade.
[0128] The battery obtained in Example 6 was subjected to charge and discharge cycles at 25 mA / cm 2Under the charging condition, the battery was charged for 5 hours and then discharged. The discharge cut-off condition was that the voltage was lower than 1V. After 100 cycles, the lead ion concentration in the remaining electrolyte and the average energy efficiency of the last five cycles were measured to be 1.418 mol / L and 96.4%, respectively.
[0129] Example 7
[0130] The electrode is pretreated before use, and a layer of lead oxide is actively deposited on its surface to improve the initial performance of the lead single-liquid flow battery and thus increase its service life.
[0131] The above coating adopts c(Pb 2+ )=1.5mol / L, deposition time is 5min, deposition current density is 10mA / cm 2 .
[0132] The above electrolyte, electrode and electrochemical deposition are carried out according to the following steps:
[0133] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0134] Step 2, electrochemically depositing the electrode in step 1 in a solution of corresponding concentration (fluoroboric acid / lead fluoroborate) at a certain current density;
[0135] Step 3: Assemble the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead single-flow battery with a longer cycle life.
[0136] Step 1 is implemented as follows:
[0137] Step 1.1, dissolve lead oxide in fluoroboric acid, stir until clear and then adjust the volume to obtain an electrolyte.
[0138] Step 1.2: Cut and grind the graphite sheet into a size of 10 mm × 10 mm, fix the back side to the copper sheet with conductive glue, and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0139] Step 2 is implemented as follows:
[0140] Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition;
[0141] Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
[0142] All chemicals used were of analytical grade.
[0143] The battery obtained in Example 7 was subjected to charge and discharge cycles at 25 mA / cm 2Under the charging condition, the battery was charged for 5 hours and then discharged. The discharge cut-off condition was that the voltage was lower than 1V. After 100 cycles, the lead ion concentration in the remaining electrolyte and the average energy efficiency of the last five cycles were measured to be 1.392 mol / L and 94.5%, respectively.
[0144] Example 8
[0145] The electrode is pretreated before use, and a layer of lead oxide is actively deposited on its surface to improve the initial performance of the lead single-liquid flow battery and thus increase its service life.
[0146] The above coating adopts c(Pb 2+ )=1.5mol / L, deposition time is 5min, deposition current density is 25mA / cm 2 .
[0147] The above electrolyte, electrode and electrochemical deposition are carried out according to the following steps:
[0148] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0149] Step 2, electrochemically depositing the electrode in step 1 in a solution of corresponding concentration (fluoroboric acid / lead fluoroborate) at a certain current density;
[0150] Step 3: Assemble the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead single-flow battery with a longer cycle life.
[0151] Step 1 is implemented as follows:
[0152] Step 1.1, dissolve lead oxide in fluoroboric acid, stir until clear and then adjust the volume to obtain an electrolyte.
[0153] Step 1.2: Cut and grind the graphite sheet into a size of 10 mm × 10 mm, fix the back side to the copper sheet with conductive glue, and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0154] Step 2 is implemented as follows:
[0155] Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition;
[0156] Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
[0157] All chemicals used were of analytical grade.
[0158] The battery obtained in Example 8 was subjected to charge and discharge cycles at 25 mA / cm 2Under the charging condition, the battery was charged for 5 hours and then discharged. The discharge cut-off condition was that the voltage was lower than 1V. After 100 cycles, the lead ion concentration in the remaining electrolyte and the average energy efficiency of the last five cycles were measured to be 1.413 mol / L and 95.1%, respectively.
[0159] Example 9
[0160] The electrode is pretreated before use, and a layer of lead oxide is actively deposited on its surface to improve the initial performance of the lead single-liquid flow battery and thus increase its service life.
[0161] The above coating adopts c(Pb 2+ )=1.5mol / L, deposition time is 5min, deposition current density is 40mA / cm 2 .
[0162] The above electrolyte, electrode and electrochemical deposition are carried out according to the following steps:
[0163] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0164] Step 2, electrochemically depositing the electrode in step 1 in a solution of corresponding concentration (fluoroboric acid / lead fluoroborate) at a certain current density;
[0165] Step 3: Assemble the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead single-flow battery with a longer cycle life.
[0166] Step 1 is implemented as follows:
[0167] Step 1.1, dissolve lead oxide in fluoroboric acid, stir until clear and then adjust the volume to obtain an electrolyte.
[0168] Step 1.2: Cut and grind the graphite sheet into a size of 10 mm × 10 mm, fix the back side to the copper sheet with conductive glue, and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0169] Step 2 is implemented as follows:
[0170] Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition;
[0171] Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
[0172] All chemicals used were of analytical grade.
[0173] The battery obtained in Example 9 was subjected to charge and discharge cycles at 25 mA / cm 2Under the charging condition, the battery was charged for 5 hours and then discharged. The discharge cut-off condition was that the voltage was lower than 1V. After 100 cycles, the lead ion concentration in the remaining electrolyte and the average energy efficiency of the last five cycles were measured to be 1.372 mol / L and 93.4%, respectively.
[0174] Comparative Example 1
[0175] This group is the reference group, and no pretreatment deposition is performed on the electrode.
[0176] The above electrolyte, electrode and electrochemical deposition are carried out according to the following steps:
[0177] Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode;
[0178] Step 2, assembling the electrode obtained in step 1 with the electrolyte;
[0179] Step 1 is implemented as follows:
[0180] Step 1.1, dissolve lead oxide in fluoroboric acid, stir until clear and then adjust the volume to obtain an electrolyte.
[0181] Step 1.2: Cut and grind the graphite sheet into a size of 10 mm × 10 mm, fix the back side to the copper sheet with conductive glue, and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
[0182] All chemicals used were of analytical grade.
[0183] The battery obtained in Example 1 was charged and discharged at 25 mA / cm 2 Under the charging condition, the battery was charged for 5 hours and then discharged. The discharge cut-off condition was that the voltage was lower than 1V. After 100 cycles, the lead ion concentration in the remaining electrolyte and the average energy efficiency of the last five cycles were measured to be 1.135 mol / L and 87.1%, respectively.
[0184] Table 1
[0185]
[0186] The electrodes obtained in Examples 1-9 and Comparative Example 1 were tested, and the results are shown in Table 1.
[0187] The experimental results show that pre-electrochemical deposition of a lead skeleton on the electrode can effectively improve its energy efficiency and service life, especially when using c(Pb 2+ )=1.0mol / L, current density is 25mA / cm 2 When the electrode is deposited under the conditions of
[0188] 98.5%, and the residual lead ion concentration is also the highest, which is 1.457mol / L, which indicates that this set of batteries can have a longer service life.
[0189] Attached Figure 1 This is a scan of the positive electrode of a lead salt single flow battery after charging only. Figure 2 This is a scan of the positive electrode of a lead salt single flow battery after a charge and discharge cycle. It can be clearly seen that there is a large amount of residual PbO after the first cycle is discharged. x Lead active material skeleton.
Claims
1. A method for increasing the service life of a lead single flow battery, characterized in that: The electrode is pre-treated by electrochemical deposition before use to actively deposit a layer of lead active substance skeleton on its surface to reduce the consumption of free lead ions in the first cycle of the battery, thereby increasing its service life.
2. The method for increasing the service life of a lead single-flow battery according to claim 1, characterized in that: Please follow the steps below to implement: Step 1, preparing a fluorine-containing boric acid electrolyte and making a graphite electrode; Step 2, electrochemically depositing the electrode in step 1 in a fluoroboric acid or lead fluoroborate solution of corresponding concentration at a certain current density; Step 3: Assembling the electrode obtained in step 2 with the electrolyte prepared in step 1 to obtain a lead salt single-flow battery with a longer cycle life.
3. The method for increasing the service life of a lead single-flow battery according to claim 2, characterized in that: Step 1 is implemented as follows: Step 1.1, dissolving lead oxide in fluoroboric acid, stirring until clear and then fixing the volume to obtain an electrolyte; Step 1.2: After cutting and polishing the graphite sheet, fix the back side to the copper sheet with conductive glue and solder it to the wire. Except for the front side of the electrode, the excess conductive part is sealed with hot melt glue to obtain a graphite electrode.
4. The method for increasing the service life of a lead single-flow battery according to claim 2, characterized in that: The step 2 is specifically implemented according to the following steps: Step 2.1, assembling the electrode and the electrolyte for electrochemical deposition; Step 2.2: Charge and deposit in a blue-electric charge and discharge system.
5. The method for increasing the service life of a lead single-flow battery according to claim 2, characterized in that: The electrolyte used for electrochemical deposition of the electrode in the electrochemical deposition is c(Pb 2+ ) is 0.5mol / L~1.5mol / L, the deposition time is 5min, and the current density used for deposition is 10mA / cm 2 ~40mA / cm 2 .
